It is Time for Indian Schools to Innovate, Invest and Disseminate Homoeopathic Education Globally (Homoeopathy for All, 2023)
The impact of the COVID-19  pandemic has continued for more  than 2 years now, and cases are still  being reported from different parts  of the world due to the emergence  of new variants like Omicron.  Simultaneously, long COVID,  defined as prolonged symptoms  after the resolution of COVID-19  infection1, has been a concern  for healthcare systems. Since the  symptoms of long COVID are diverse  and underlying mechanisms are  not very clear, a standard treatment  to combat its manifestations does  not exist. While dependency on  bronchodilators and beta blockers  exists with variable results, the public  has been moving towards using safer  alternative therapies that could build  resilient body systems and strengthen  them internally.
Keywords: variants; systems; internally